Design of an instrumentation for the automated damage detection in ceilings. (March 2018) - Belletti, B.; Berardengo, M.; Collini, L.; Foresti, R.; Garziera, R.
Abstract: A diagnosis method for the detection of detachments occurring in ceilings made with the system beam-and-clay is presented. This analysis is carried out by an innovative, portable instrument. The apparatus is capable of automatically tapping a small area of the ceiling by the shot of a controlled-energy pin, and of simultaneously detecting the out of plane vibration of this area by a low-cost digital accelerometer. Different "levels" in vibration correspond to different movability for the ceiling. By comparing these movabilities, we are able to indicate detachment and its severity/extension. Results of a 1-year experimental campaign in schoolrooms encourage further development and widespread application of the instrument.